2018
DOI: 10.5603/fhc.a2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases-2, -7 and tissue metalloproteinase inhibitor-1 expression in human endometrium

Abstract: The results of the study indicate that estradiol influence MMP-2 expression in the endometrium depends on the phase of menstrual cycle. Such relationships were not found for MMP-7 and TIMP-1 and further tests clarifying association between estradiol and MMPs are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…MMP2 is a confirmed miR-29c target in lung cancer 18 . Its expression is reported to be highest in the fertile proliferative phase, suggesting a role in endometrial remodelling 28 . It has also been reported MMP2 expression during receptivity is dysregulated with infertility 29 .…”
Section: Discussionmentioning
confidence: 99%
“…MMP2 is a confirmed miR-29c target in lung cancer 18 . Its expression is reported to be highest in the fertile proliferative phase, suggesting a role in endometrial remodelling 28 . It has also been reported MMP2 expression during receptivity is dysregulated with infertility 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, it is demonstrated that the cultured CD146 + human endometrial cells in the collagen/matrigel scaffold in the presence of MSMCs resulted in the expression of ZO-1, COL4A1, and LAMA2 genes at the mRNA level as well as the formation of glandular-like structures at the morphological and ultrastructural levels [19]. The osteopontin (SPP1) and matrixmetaloproteinase-2 (MMP2) proteins are secreted by the endometrial epithelial and stromal cells [27][28][29][30][31]. Osteopontin plays a role in embryo implantation, placenta formation, cell-to-cell adhesion, and proliferation and migration of endometrial cells [27][28][29] and the MMP proteases have an essential function in endometrial tissue remodeling during the menstrual cycle [30][31].…”
Section: Discussionmentioning
confidence: 84%
“…The osteopontin (SPP1) and matrixmetaloproteinase-2 (MMP2) proteins are secreted by the endometrial epithelial and stromal cells [27][28][29][30][31]. Osteopontin plays a role in embryo implantation, placenta formation, cell-to-cell adhesion, and proliferation and migration of endometrial cells [27][28][29] and the MMP proteases have an essential function in endometrial tissue remodeling during the menstrual cycle [30][31]. Myometrial cells secrete some factors, ECM components, and substances that play an inductive role in the epithelialization of human endometrial tissue as well as cell proliferation, differentiation, migration, attachment, polarity, and apoptosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Further Grzechocinska et al demonstrated how there was an absence of association among lack of correlation between proMMP-2 along with MMP-2 amounts point that separate pathway of their activation in AUB. ProMMP-2 is up regulated by estradiol and down regulated by progesterone while MMP-2 levels increase with the length of bleeding [143]. This way with knowledge given by Johanns et al with regards to Cellular uptake of proMMP-2:TIMP-2 complexes by the endocytic receptor megalin/LRP-1 ,with earlier knowledge on how low-density lipoprotein receptor-related protein-1 (LRP-1) mediates the clearance of a complex between the zymogen form of MMP-2 (proMMP-2) and tissue inhibitor of metalloproteinases, TIMP-2, in HT1080 human fibrosarcoma cells .…”
Section: Discussionmentioning
confidence: 98%